(untitled) (Journal of the Management Sciences, 2025)
This study examined the effects of job burnout—specifically workload and role ambiguity—on employee performance at Star Glass Beverages Nigeria Limited, Ogun State. Growing work pressures in the manufacturing sector have heightened concerns about employee well-being, productivity, and effectiveness. Using a survey research design, structured questionnaires were administered to 112 employees, out of which 101 valid responses were analyzed using descriptive statistics and regression analysis via SPSS. Findings revealed that workload has a significant negative effect on employee productivity (β = –2.729; R² = 0.452, p < 0.05), indicating that excessive job demands reduce employees’ ability to deliver optimal output. Similarly, role ambiguity showed a significant negative effect on employee effectiveness (β = –0.010; R² = 0.398, p < 0.05), suggesting that unclear job responsibilities contribute to confusion, stress, and diminished task performance. These results confirm that job burnout is a critical challenge that undermines both productivity and effectiveness within the organization. The study concludes that addressing burnout—by reducing excessive workload and clarifying job roles—is essential for improving employee performance. It recommends that management implement strategies such as task redistribution, clearer communication of job expectations, enhanced supervisory support, and possible recruitment of additional staff to strengthen employee well-being and organizational competitiveness.